Advances in ceramics for environmental, functional, structural, and energy applications - Mahmoud, Morsi M.; Sridharan, Kumar; Colorado, Henry; Bhalla, A. S., 1943-; Singh, J. P.; Gupta, Surojit; Langhorn, Jason; Jitianu, Andrei; Manjooran, Navin (Ceramic transactions, 2018)
This volume contains 20 manuscripts presented during the Materials Science & Technology 2017 Conference (MS & T'17), held October 8-12, 2017 at the David L. Lawrence Convention Center, Pittsburgh, PA. Papers from the following symposia are included in this volume: 9th International Symposium on Green and Sustainable Technologies for Materials Manufacturing and Processing ; Advances in Dielectric Materials and Electronic Devices ; Construction and Building Materials for a Better Environment ; Innovative Processing and Synthesis of Ceramics, Glasses and Composites ; Materials Issues in Nuclear Waste Management in the 21st Century ; Materials Development for Nuclear Applications and Extreme Environments ; Materials for Nuclear Energy Applications ; Nanotechnology for Energy, Healthcare and Industry ; Processing and Performance of Materials Using Microwaves, Electric and Magnetic Fields, Ultrasound, Lasers, and Mechanical Work: Rustum Roy Symposium.